Stakeholder Relationship Management Strategy to Improve the Quality of Education Services - Gabriela Vanesa Mutiarani; Hafidzah Nur’Abidah (Professorline, 2026)
Stakeholder relationship management is one of the important aspects in the implementation of education that is oriented towards improving service quality. Stakeholders in education include internal and external parties, such as educators, students, parents, the government, the business world, and the community. Strategically managed relationships can create harmonious cooperation, increase trust, and strengthen support for educational programs. Actionable strategies include transparent communication, active participation in decision-making, and strengthening ongoing partnerships. In addition, the use of information technology also plays a role in increasing the effectiveness of coordination and information delivery between stakeholders. The implementation of an effective stakeholder relationship management strategy is expected to be able to improve the quality of education services as a whole, both from academic and non-academic aspects, so that educational institutions can produce graduates who are competent, adaptive, and in accordance with the needs of the community.